Pengaruh Kualitas Sumber Daya Manusia, Kualitas Kerja, Profesionalisme Kerja dan Komitmen Terhadap Peningkatan Kinerja Karyawan PDAM Kota Malang - Yurina Khusnal Amaliyyah; Nurhajati Nurhajati; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine how the influence of human resource quality, work quality, work professionalism and commitment to the performance of PDAM Malang City employees. The dependent variable in this study is performance. And there are 4 independent variables used, namely the quality of human resources, quality of work, work professionalism and commitment. The population in this study were employees of PDAM Malang City. The sample in this study was taken using saturated sampling technique. The data collection method used is the method of distributing questionnaires to respondents. The data analysis technique used in this study is multiple linear regression. The results of the study indicate that simultaneously the variables of human resource quality, work quality, work professionalism and commitment have a significant effect on performance. Meanwhile, partially, the variable of the quality of human resources has a negative and insignificant effect on performance. The work quality variable has a positive and significant effect on performance. Work professionalism variable has a negative and significant effect on performance. And the commitment variable has a positive and significant effect on performance. Keywords: quality of human resources, quality of work, work professionalism, commitment and performance